Mechanistic insights into defect chemistry and tailored photoluminescence and photocatalytic properties of aliovalent cation substituted Zn0.94M0.06−xLixO (M: Fe3+, Al3+, Cr3+) nanoparticles. Issue 41 (4th October 2021) - Ansari, Sajid Ali; Manjunatha, C.; Parveen, Nazish; Shivaraj, B. W.; Hari Krishna, R.
Abstract : Mechanism for photocatalytic degradation of rhodamine B dye on the doped ZnO photocatalyst. Abstract : In this work, we demonstrate the microwave assisted solution combustion synthesis of aliovalent cation substituted Zn0.94 M0.06− x Li x O (M: Fe 3+, Al 3+, Cr 3+ ) nanoparticles. The structural features, photoluminescence and photocatalytic properties were characterized by X-ray powder diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and UV-visible and photoluminescence (PL) techniques. We have introduced aliovalent cations such as reducible Fe 3+, stable Al 3+ and oxidisable Cr 3+ ions into ZnO and investigated its structural and optical properties. The charge balance and defect stoichiometric composition of ZnO were also studied by co-doping with Li + ions. By understanding the photoluminescence and photocatalytic activity of doped and co-doped ZnO nanoparticles, the defect chemistry of ZnO is explained in detail. The photocatalytic efficiency of various doped and co-doped ZnO catalysts was compared with respect to the degradation of rhodamine B dye. Among them, the CZO, AZO and L3AZO catalysts showed enhanced photo-degradation efficiencies of 98.1%, 97.6% and 96.6%, respectively, which are high as compared to that of ZnO (89%). This work presents a novel and straightforward, low-cost, tunable and scalable fabrication protocol for highly efficient ZnO-based photocatalysts for practical applications.